Gambaran Penolakan Pendonor Pria dengan Hipertensi Derajat 2 - Katarina Atagoran; Dian Astarini (PT. Promosi Kesehatan Media, 2026)
Background: Grade 2 hypertension is one of the main causes of blood donation rejections, as blood pressure exceeds the recommended limit. This condition poses a health risk to donors and can impact blood availability at the Indonesian Red Cross Blood Transfusion Unit (UTD PMI) in Yogyakarta City. Objective: This study aims to determine the rejection rate of male donors with grade 2 hypertension based on age, blood type, and donor status (new or repeat) in 2025. Methods: This quantitative descriptive study used a retrospective study design. The study population included all 37,887 male donors at the UTD PMI in Yogyakarta City in 2025. The sample was drawn using a total sampling technique, including all 1,270 male donors rejected due to grade 2 hypertension. Data analysis used a frequency distribution in percentage form. Results and Discussion: Donor rejection due to grade 2 hypertension was most common in the 46–60 age group (701 donors (55.2%), with blood type O (507 donors (40.0%), and with repeat donor status (1,185 donors (93.3%). Conclusion: In 2025, rejections of male donors with grade 2 hypertension at the Indonesian Red Cross (PMI) Blood Transfusion Unit (UTD) in Yogyakarta City were dominated by the 46–60 age group, blood type O, and repeat donors. Screening efforts, ongoing health education, and promotive and preventive programs are needed to reduce the rate of donor rejections.